The Settlement Model of Non-Performing Financing Which is More Effective and Legal Justice in Sharia Financing Companies - Trianah Sofiani; Heris Suhendar (Unissula, 2024)
Post-pandemic COVID-19 still leaves Non-Performing Financing (NPF), especially financing with fiduciary guarantees in Sharia finance companies. The Otoritas Jasa Keuangan's Relaxation Policy, which ended in April 2023, has not been effective and has fulfilled a sense of justice for debtors. This research discusses the causes of the ineffective implementation of the Relaxation policy in Sharia Financing Companies so that there is still NPF post the Covid-19 pandemic. Furthermore, it discusses the settlement model of NPF as an offer so that is more effective and fulfils a sense of justice for the parties. This empirical juridical research uses a qualitative approach in collaboration with statutory and conceptual approaches. The research locations were nineteen financing companies in Pekalongan ex-Residency with fiduciary financing objects. Data collection uses focus group discussions, interviews and document studies. The results show that inconsistent norms, negative legal culture, misperceptions of restructuring diction as the write-off of debt and the debtor's objection in the settlement of NPF are the causes of the ineffective implementation of the Relaxation policy. The settlement of NPF should be carried out based on sharia principles, the principle of prudence and good faith which prioritizes the needs of the debtor. Determining the rescheduling period should be carried out using a tri-semester tiered model so that effectivity, justice and benefits (reciprocal benefits) will be realized between the two parties.